1999
DOI: 10.1007/bf02358387
|View full text |Cite
|
Sign up to set email alerts
|

The potential for production of high quality seed potatoes in Tierra del Fuego Island, Argentina

Abstract: SummaryIn Argentina, different areas are suitable for seed potato production: however, each has particular problems, mainly related to different pest and diseases. Tierra del Fuego Island is well isolated from traditional potato growing areas. Therefore, it was tested for its potential for seed production.The cultivars Achatt, Mail6n INTA, Pampeana INTA and Spunta were grown in Rio Grande, San Pablo and Ushuaia from 1991-1994. Nematode presence and aphid population dynamics were recorded. Average tuber yield r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
1
7
0
3
Order By: Relevance
“…The use of pre-sprouted and physiologically old seed is a pre-requisite to achieve acceptable tuber yield in such a short growing season and no YRF's have been identified. The results of Caldiz et al (1999) indicated an average yield of 22 t ha-I. During the period 1960-1985 cvs Huinkul MAG and Ballenera MAA accounted for more than 80% of the Argentinian market.…”
Section: The Southeast Of the Buenos Aires Province At Present Seed mentioning
confidence: 98%
See 4 more Smart Citations
“…The use of pre-sprouted and physiologically old seed is a pre-requisite to achieve acceptable tuber yield in such a short growing season and no YRF's have been identified. The results of Caldiz et al (1999) indicated an average yield of 22 t ha-I. During the period 1960-1985 cvs Huinkul MAG and Ballenera MAA accounted for more than 80% of the Argentinian market.…”
Section: The Southeast Of the Buenos Aires Province At Present Seed mentioning
confidence: 98%
“…Occidental and persistent winds are predominant in the Magallanic Steppe, an arid environment, where only 10 ha have been grown in the "Jos6 Men6ndez" farm. A recent paper by Caldiz et al (1999) demonstrated, after three years of research, that the area is free from nematodes and the aphid population is very low. Crops must be grown from mid October-January in order to escape frosts.…”
Section: The Southeast Of the Buenos Aires Province At Present Seed mentioning
confidence: 98%
See 3 more Smart Citations